UPAYA MENINGKATAN PRESTASI BELAJAR SISWA MELALUI METODE KOOPERATIF JIGSAW PADA MATA PELAJARAN BAHASA INDONESIA SISWA KELAS IX SMP NEGERI 1 TANJUNG MORAWA - Florida Simatupang; Rita Masdiana Manurung (Jurnal Dedikasi Pendidikan, 2021)
In the Bahasa Indonesian lesson, the students’ skills low in compiling the text structure of reports were still low. Many students do not structure the report properly and correctly. In evaluating many students' scores below the KKM. Students seem less enthusiastic and not ready to take lessons on the material of the text structure of reports so that the class atmosphere became passive and the learning process was conventional and not varied. This classroom action research aims: 1) To determine the application of the Jigsaw Cooperative Method in improving students' skills in compiling the text structure of reports of class IX on odd semester SMP Negeri 1 Tanjung Morawa; 2) To know the students’ improvement in compiling the text structure of reports of class IX students in the odd semester of SMP Negeri 1 Tanjung Morawa through the application of the Jigsaw Cooperative Method; 3) How is the response of student class IX odd semester of SMP Negeri 1 Tanjung Morawa in Bahasa Indonesian lesson in the Material of Report Text through the application of the Jigsaw Cooperative Method. This research was conducted using interactive qualitative methods and Classroom Action Research (CAR) which was conducted in 2 cycles. Each cycle included planning, implementation, observation, and reflection. The subjects of this classroom action research were the students of class IX odd semester SMP Negeri 1 Tanjung Morawa Kab. Deli Serdang. While the object was the Jigsaw Cooperative Method. Based on the data analysis, it can be concluded that in cycle 1 the students' learning completeness in this material is only 69.29, while in cycle 2 by applying the Jigsaw Cooperative Method learning strategy, it increases in cycle 2 the average value increases to 87.14. Students’ responses also increased. It based on the data from observations of student activity from 52.08% in cycle 1, increased in cycle 2 to 89.58%.